Different Aspects of Behçet's Disease - Gönül, Müzeyyen; Kılıç, Arzu (IntechOpen, 2020)
The aim of this book is to give readers a different review of Behçet's disease, which has very rich mucocutaneous and systemic characteristics and can be confused with many diseases. This book has a total of five chapters. The first two chapters focus on an overview of Behçet's disease, the next two chapters focus on important pathogenetic factors and genetic and immunologic pathogenesis of the disease, and the last chapter looks at the relationship between pregnancy and Behçet's disease. We are grateful to all the contributors and leading experts for their valuable chapters, which provide an in-depth view of all aspects of the content, backed up with the most current literature in the field.